The Development of Physics Digital Comics on Temperature and Heat Material to Improve The Critical Thinking Ability - Devi Retno Rosdiana; Abd. Kholiq (Universitas Lambung Mangkurat, 2021)
This study was conducted to develop temperature and heat learning media for high school students to improve their critical thinking skills regarding the phenomena related to temperature and heat material. This study uses the DDDE (Decide, Design, Development, Evaluation) method. This research begins with the stages of determining digital comics as learning media, compiling storylines and sketching comic images, compiling complete comics along with character dialogues, and evaluating the final results of digital comics. Three validators carried out validation test. The results of the validation test showed that digital comics were significantly suitable to be used as supporting media for temperature and heat learning based on several criteria, including learning aspects of 89.78%, material aspects of 93%, and media aspects 93.17%. These digital comics were consequently suitable to be used as a medium for supporting online learning and had time efficiency in delivering material. The implication of this study will facilitate the teaching and learning process from home or School from Home (SFH) during the pandemic period and is expected to be developed in further studies.